How (Not) to Reproduce: Practical Considerations to Improve Research Transparency in Political Science. Issue 1 (16th January 2022) - Alvarez, R. Michael; Heuberger, Simon
ABSTRACT: In recent years, scholars, journals, and professional organizations in political science have been working to improve research transparency. Although better transparency is a laudable goal, the implementation of standards for reproducibility still leaves much to be desired. This article identifies two practices that political science should adopt to improve research transparency: (1) journals must provide detailed replication guidance and run provided material; and (2) authors must begin their work with replication in mind. We focus on problems that occur when scholars provide research materials to journals for replication, and we outline best practices regarding documentation and code structure for researchers to use.